THE ROLE OF ISLAMIC RELIGIOUS EDUCATION TEACHERS IN FOSTERING STUDENTS' RELIGIOUS VALUES (Field Study at SMP Negeri 2 Kesugihan) - Rofiqotul Mukaromah; Ulil Albab (TSURAYYA: Journal Education, Economy and Religia, 2026)
Islamic religious education in schools has often been considered unsuccessful in fostering students' religious values. The lack of awareness and indifference of each individual to religion is one of the factors that underachieves Islamic religious education in schools. This study aims to find out the role of Islamic Religious Education teachers and the factors faced by Islamic Religious Education teachers in fostering students' religious values at SMP N 2 Kesugihan. This research is a type of field research. The approach used is a qualitative research method. Data was collected through observation, interview, and documentation methods. The subjects of this study are the principal of SMP N 2 Kesugihan, curriculum waka, Islamic Religious Education teachers and students of SMP N 2 Kesugihan. The data analysis applied is data reduction, data presentation and verification. The validity test of the data was carried out through a credibility test technique which included increasing diligence in observation and triangulation. This study concludes that the role of Islamic Religious Education teachers in fostering students' religious values at SMP N 2 Kesugihan is inseparable from the main duties of the teachers themselves, namely by optimizing the role and duties of Islamic Religious Education teachers which are integrated in the learning process, optimizing several religious habits that are always carried out, including praying before and after learning, tadarus Al-Qur'an, congregational dzuhur prayer, reading Asmaul Husna and morning literacy, creating a religious learning atmosphere and school environment and becoming an exemplary figure for students.